Fast Proton Insertion in Layered H2W2O7 via Selective Etching of an Aurivillius Phase. Issue 1 (23rd November 2020) - Wang, Ruocun; Sun, Yangyunli; Brady, Alexander; Fleischmann, Simon; Eldred, Tim B.; Gao, Wenpei; Wang, Hsiu‐Wen; Jiang, De‐en; Augustyn, Veronica
Abstract: H2 W2 O7, a metastable material synthesized via selective etching of the Aurivillius‐related Bi2 W2 O9, is demonstrated as an electrode for high power proton‐based energy storage. Comprehensive structural characterization is performed to obtain a high‐fidelity crystal structure of H2 W2 O7 using an iterative approach that combines X‐ray diffraction, neutron pair distribution function, scanning transmission electron microscopy, Raman spectroscopy, and density functional theory modeling. Electrochemical characterization shows a capacity retention of ≈80% at 1000 mV s –1 (1.5‐s charge/discharge time) as compared to 1 mV s –1 (≈16‐min charge/discharge time) with cyclability for over 100 000 cycles. Energetics from density functional theory calculations indicate that proton storage occurs at the terminal oxygen sites within the hydrated interlayer. Last, optical micrographs collected during in situ Raman spectroscopy show reversible, multicolor electrochromism, with color changes from pale yellow to blue, purple, and last, orange as a function of proton content. These results highlight the use of selective etching of layered perovskites for the synthesis of metastable transition metal oxide materials and the use of H2 W2 O7 as an anode material for proton‐based energy storage or electrochromic applications. Abstract : H2 W2 O7, a metastable material synthesized via selective etching of the Aurivillius‐related Bi2 W2 O9, can serve as an electrode for high power aqueous proton‐based energy storage with sub‐minute charging time and cyclability over 100 000 cycles. It highlights the use of selective etching of layered perovskites for the synthesis of metastable transition metal oxide for energy storage applications.